Prevalence of alternative lengthening of telomeres in pediatric sarcomas determined by the telomeric DNA C-circle assay - Burrow, Trevor A.; Koneru, Balakrishna; Macha, Shawn J.; Sun, Wenyue; Barr, Frederic G.; Triche, Timothy J.; Reynolds, C. Patrick (Frontiers in Oncology, 2024)
Introduction: Alternative lengthening of telomeres (ALT) occurs in sarcomas and ALT cancers share common mechanisms of therapy resistance or sensitivity. Telomeric DNA C-circles are self-primed circular telomeric repeats detected with a PCR assay that provide a sensitive and specific biomarker exclusive to ALT cancers. We have previously shown that 23% of high-risk neuroblastomas are of the ALT phenotype. Here, we investigate the frequency of ALT in Ewing’s family sarcoma (EFS), rhabdomyosarcoma (RMS), and osteosarcoma (OS) by analyzing DNA from fresh frozen primary tumor samples utilizing the real-time PCR C-circle Assay (CCA). Methods: We reviewed prior publications on ALT detection in pediatric sarcomas. DNA was extracted from fresh frozen primary tumors, fluorometrically quantified, C-circles were selectively enriched by isothermal rolling cycle amplification and detected by real-time PCR. Results: The sample cohort consisted of DNA from 95 EFS, 191 RMS, and 87 OS primary tumors. One EFS and 4 RMS samples were inevaluable. Using C-circle positive (CC+) cutoffs previously defined for high-risk neuroblastoma, we observed 0 of 94 EFS, 5 of 187 RMS, and 62 of 87 OS CC+ tumors. Conclusions: Utilizing the ALT-specific CCA we observed ALT in 0% of EFS, 2.7% of RMS, and 71% of OS. These data are comparable to prior studies in EFS and OS using less specific ALT markers. The CCA can provide a robust and sensitive means of identifying ALT in sarcomas and has potential as a companion diagnostic for ALT targeted therapeutics.